2017
DOI: 10.1098/rsob.160333
|View full text |Cite
|
Sign up to set email alerts
|

Parallel analysis ofArabidopsiscircadian clock mutants reveals different scales of transcriptome and proteome regulation

Abstract: The circadian clock regulates physiological processes central to growth and survival. To date, most plant circadian clock studies have relied on diurnal transcriptome changes to elucidate molecular connections between the circadian clock and observable phenotypes in wild-type plants. Here, we have integrated RNA-sequencing and protein mass spectrometry data to comparatively analyse the lhycca1, prr7prr9, gi and toc1 circadian clock mutant rosette at the end of day and end of night. Each mutant affects specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 119 publications
(212 reference statements)
6
89
0
Order By: Relevance
“…Significant protein phosphorylation changes were most frequently found in flowers (ED) and in rosettes (EN), whereas significant protein acetylation changes were most abundant in roots (ED) and in seedlings (EN) (Data S2; Table ). In contrast, few proteins in the proteomes from the same organs and seedlings had a Log2‐fold abundance change of >1.0 at the corresponding time points (Data S3), consistent with previous reports (Baerenfaller et al ., ; Graf et al ., ; Seaton et al ., ). To determine whether the observed changes in PTM levels resulted from changes in protein abundance we compared the quantified PTMome and total proteome.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Significant protein phosphorylation changes were most frequently found in flowers (ED) and in rosettes (EN), whereas significant protein acetylation changes were most abundant in roots (ED) and in seedlings (EN) (Data S2; Table ). In contrast, few proteins in the proteomes from the same organs and seedlings had a Log2‐fold abundance change of >1.0 at the corresponding time points (Data S3), consistent with previous reports (Baerenfaller et al ., ; Graf et al ., ; Seaton et al ., ). To determine whether the observed changes in PTM levels resulted from changes in protein abundance we compared the quantified PTMome and total proteome.…”
Section: Resultsmentioning
confidence: 98%
“…Our current understanding of circadian and light control is largely derived from genetic and transcriptomic studies, which have revealed the extent to which the expression of genes is regulated by the clock and the diurnal cycle (Endo et al, 2014;Greenham and McClung, 2015;Nagel et al, 2015;Nohales and Kay, 2016). More recent studies have shown that transcript and protein abundance may not always be correlated at the light-dark transitions during the diurnal cycle, indicating that transcriptional changes are not necessarily predictive for regulation at the protein level (Baerenfaller et al, 2012;Graf et al, 2017;Seaton et al, 2018). Moreover, it is currently unknown if this lack of coincident transcript and protein-level regulation also extends to proteins whose function is circadian clock-or light controlled by phosphorylation or acetylation, or both.…”
Section: Introductionmentioning
confidence: 99%
“…46 Analysis of the Arabidopsis proteome revealed that 30-40% of proteins with rhythmic protein levels do not have rhythmic transcripts, 70 implicating translation and turnover in generating these rhythms. Meanwhile, many rhythmic mRNAs have no detectable protein rhythm, 44,45 suggesting that Model 2 applies. Moreover, comparing between liver and kidney, ribosome occupancy is more similar than mRNA transcript levels for a large number of genes.…”
Section: Mechanistic Reasons For Rhythms Of Translationmentioning
confidence: 99%
“…If our goal is to not just measure and understand, but also to predict and control 83 diel cycles of gene expression, then we require corresponding quantitative mathematical models of gene expression that are founded on a rigorous theoretical framework from molecular biochemistry. Specifically, diurnal protein levels 30,40,41,44,45,70,84 are determined by rates of mRNA synthesis and mRNA degradation, mRNA translation (protein synthesis), and protein turnover. Regarding these processes, the more widely available data are on mRNA transcript levels, 85,86 which are the dynamic balance between transcription and turnover, in the same way that protein levels are the dynamic balance of protein synthesis and protein turnover.…”
Section: Mechanistic Reasons For Rhythms Of Translationmentioning
confidence: 99%
See 1 more Smart Citation